Multiscale molecular modeling of SWCNTs/epoxy resin composites mechanical behaviour - Ionita, Mariana (Composites. Part B, Engineering, 2012)
Atomistic and mesoscale simulations were conducted to estimate the effect of the diameter and weight fraction of single walled carbon nanotubes (SWCNTs) on mechanical behaviour and glass transition temperature (Tg) of SWCNTs reinforced epoxy resin composites. Atomistic periodic systems of epoxy resin and epoxy resin/SWCNTs were built with different weight ratios and were subject of an extensive multistage equilibration procedure. Molecular dynamics simulations were used to estimate glass transition temperature, Young modulus and solubility parameter of epoxy resin and epoxy resin/SWCNTs composites. Dissipative particle dynamics method and Flory–Huggins theory was employed to predict epoxy resin/SWCNTs morphologies. The results show that incorporation of SWCNTs with diameters ranging from 10 to 14Ǻ has beneficial effect on mechanical integrity and Tg. Overall, the agreement between predicted material properties and experimental data in the literature is very satisfactory.